TRANSITIVITY SYSTEMS ANALYSIS OF ENGLISH FOR VOCATIONAL HIGH SCHOOL (SMK) OF SOSORGADONG TEXTBOOK FOR GRADE X AND ITS RELEVANCE TO ENGLISH LANGUAGE TEACHING - Gusman Keizer Bondar; I Wayan Dirgeyasa Tangkas; Eddy Setia (LINGUISTIK TERAPAN, 2019)
There are two problems proposed in this paper, i.e. about (1) the transitivity systems elements that characterize English for SMK 1 Textbook for Grade X, and (2) the relevance of transitivity elements (Process and Circumstance) with the English teaching and learning processes. By using the theory of SFL, it can be described (as qualitative descriptive method of research), that in all Units of reading texts in the English textbook there were 238 clauses selected methodologically to be analyzed. In these clauses, all Process Types can be found with varieties of the usage. It is found that in all units of reading texts, Material Process types was the dominant type used, i.e. (48.6%), followed by Relational Process type (27,2%), Mental Process (18.6%) Verbal Process type 8,4%, and Behavioral and Existentional 7.0% each respectively. Related to the circumstance, the dominant one is Circumstance of Location (Time and Place = 37.7%). For the participant, it is related to the process exists in the text, i.e. Actor for Participant 1 and Goal for Paticipant 2.Keyword: Transitivity Systems Analysis, Textbook, Vocational High School